2016
DOI: 10.1371/journal.pntd.0004728
|View full text |Cite
|
Sign up to set email alerts
|

First Human Cases of Leishmania (Viannia) lainsoni Infection and a Search for the Vector Sand Flies in Ecuador

Abstract: An epidemiological study of leishmaniasis was performed in Amazonian areas of Ecuador since little information on the prevalent Leishmania and sand fly species responsible for the transmission is available. Of 33 clinical specimens from patients with cutaneous leishmaniasis (CL), causative parasites were identified in 25 samples based on cytochrome b gene analysis. As reported previously, Leishmania (Viannia) guyanensis and L. (V.) braziliensis were among the causative agents identified. In addition, L. (V.) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
2
18
0
1
Order By: Relevance
“…(V . ) lainsoni were identified in this study; all were reported previously in Ecuador, the latter two rather recently [ 7 , 8 ] ( Table 1 , Fig 1 ). Cases of L .…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…(V . ) lainsoni were identified in this study; all were reported previously in Ecuador, the latter two rather recently [ 7 , 8 ] ( Table 1 , Fig 1 ). Cases of L .…”
Section: Resultssupporting
confidence: 76%
“…(V . ) braziliensis was identified as the dominant species as reported previously [ 5 , 8 , 9 ]. In addition, other species, L .…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Leishmania major ( L. major ), Leishmania tropica ( L. tropica ) in the old world as well as species belonging to Leishmania mexicana ( L. mexicana ) complex and subgenus of Leishmania Viannia, in the new world, are assumed to be the most aetiological factors of the CL . This disease is transmittable through female sand flies and commonly results in localized lesions.…”
Section: Introductionmentioning
confidence: 99%
“…(V.) braziliensis não são bons reservatórios deste parasito (MADEIRA et al, 2005(MADEIRA et al, , 2006CASTRO et al, 2007) LAINSON et al 1994;AZEVEDO et al, 2002, TOJAL et al, 2003, CÓRDOVA et al, 2011BRASIL, 2013;PIRES et al, 2015;TELES et al, 2016;KOARASHI et al, 2016 A espécie Ny. umbratilis (Ward & Fraiha, 1977), principal vetor suspeito, espécie com ampla distribuição na Amazônia, podendo ser encontrada em florestas primárias, principalmente em troncos de árvores, e que são altamente antropofílicas (LAINSON et al, 1994 Peru (LUCAS et al, 1994;MARTINEZ et al, 2001;TOJAL et al, 2006;TELES et al, 2015) e recentemente no Equador (KATO et al, 2016). Possui como reservatório a paca (Agouti paca) e como principal vetor, Th.…”
Section: Manuscritounclassified